Threshold of Toxicological Concern (TTC) for Botanical Extracts (Botanical-TTC) derived from a meta-analysis of repeated-dose toxicity studies. (November 2019) - Kawamoto, Taisuke; Fuchs, Anne; Fautz, Rolf; Morita, Osamu
Highlights: 213 Point-of-Departures on botanical extracts were collected. Cramer III TTC can be considered as conservative enough for botanical extracts. A novel TTC value of 663 μg/day for botanical extracts is proposed. Abstract: Threshold of Toxicological Concern (TTC) is a promising approach for evaluating the human health risk for systemic toxicity when there is a lack of toxicological information. The threshold for systemic toxicity is reportedly 1800, 540, and 90 μg/day for Cramer I–III chemical structures, according to Munro's structural decision tree, and 0.15 μg/day for genotoxic compounds. However, the concept of TTC has been developed for single substances; therefore, the applicability of TTC for mixtures remains unclear. To expand application of probability approach for mixtures, a validation study using the point of departures (PoDs) derived from mixtures is required. In the present study, we investigated novel TTC of botanical extracts (Botanical-TTC) for cosmetics from a meta-analysis based on the PoDs derived from repeated dose toxicity testing in botanical extracts. Accordingly, 213 PoDs were determined by repeated-dose toxicity studies and divided using a default uncertainty factor of 100 combined with the extrapolation factor of study duration to calculate the derived-no-effect-level (DNEL) and derived-minimal-effect-level (DMEL). The minimum DNEL/DMEL was 1.6-fold higher than the Cramer III TTC. In addition, because human health risk below the 1 st percentile value (663 μg/day) was considered as extremely limited, the exposure level can be proposed as Botanical-TTC.